Origene, il pozzo di Giacobbe e l’άνήρ della samaritana - Simonetti, Manlio (Augustinianum, 2016)
With regard to the interpretation of the conversation between Jesus and the Samaritan woman examined by Origen in Book 13 of the Commentary on John, in this study the Author analyzes certain terms (e.g. φρέαρ, πηγή, άνήρ, νόμος) or expressions (e.g. "you spoke the truth there", Io. 4, 18) on which Origen’s analysis focuses, and he concludes that the great Alexandrian exegete does not seem to show his best skills in these explanations.